Dehydration-associated cerebral hypoperfusion in sudden sensorineural hearing loss: an arterial spin labeling-based preliminary study - Shrestha, Palpasa; Wen, Zhi; Zheng, Anyuan; Yang, Xilin; Liao, Hua; Ramjaun, Mohamed Muntasir; You, Cixing; Shrestha, Jati; Yang, Renjie; Chen, Jun (Frontiers in Neurology, 2025)
ObjectiveSudden sensorineural hearing loss (SSNHL) rapidly decreases hearing, often by more than 30 decibels within 3 days. While circulatory issues are suspected causes, the exact reason remains unclear. This study employs Arterial Spin Labeling to examine changes in cerebral blood flow and its relationship with hydration levels in SSNHL.MethodsA prospective study examined patients with SSNHL, dividing them into 20 right-sided SSNHL (RSSNHL), 22 left-sided SSNHL (LSSNHL), and 20 healthy controls (HC). Cerebral blood flow (CBF) data were obtained using MATLAB. Statistical analysis included one-way ANOVA with post hoc analysis among RSSNHL, LSSNHL, HC, and Pearson correlation to explore the relationship with clinical variables.ResultsCompared to HC, patients with RSSNHL showed reduced CBF value in right medial superior frontal gyrus, Heschl's gyrus (HG), and left inferior temporal gyrus, conversely increased perfusion in left calcarine. In LSSNHL patients, CBF value was decreased in the left superior temporal gyrus (STG) and right middle temporal gyrus, with increased perfusion in the left temporal pole STG compared to HC (cluster level P < 0.05 after FDR correction). Furthermore, CBF in the right HG of RSSNHL and left STG of LSSNHL negatively correlated with blood viscosity (r = −0.621, P = 0.003; r = −0.560, P = 0.007) and urine specific gravity (r = −0.483, P = 0.031; r = −0.485, P = 0.022), and positively correlated with daily water intake (r = 0.650, P = 0.002; r = 0.568, P = 0.006).ConclusionCerebral perfusion changes were present in the temporal, frontal, and occipital lobes of SSNHL patients. Furthermore, insufficient water intake may be a potential cause of SSNHL. Drinking adequate water is vital in preventing and recovering from this condition.